Voltammetric Studies of Cobalt Hexacyanoferrate Formed on the Titanium (IV) Phosphate Surface and its Application to the Determination of Sulfite - Cumba, Loanda Raquel [UNESP] (2012)
Titanium (IV) Phosphate (TiPh) composite was prepared using a easily methodology of the synthesis. As a second step, TiPh was reacted with Cobalte (TiPhCo) and subsequent hexacyanoferrate was added (TiPhCoHCF). A preliminary characterization of the precursor and resulting materials was carried out using spectroscopic and voltammetric techniques. The electrochemical behaviour of the composite (TiPhCoHCF) was verified by means of a graphite paste electrode using cyclic voltammetry in a potential range of -0.2 to 1.0 V (vs Ag/AgCl). The cyclic voltammogram of the modified electrode containing TiPhCoHCF exhibited two redox couples. The first process (peak I) presented a formal potential (E-theta') = 0.37 V vs Ag/AgCl attributed to the redox process Co-(II) / Co-(III) and other more defined redox couple, (peak II), showed a E theta' = 0.67 V vs Ag/AgCl which was attributed to the redox process [Fe-(II)(CN)(6)] /[Fe-(III)(CN)(6)]. The second redox couple exhibited an electrocatalytic activity towards the oxidation of sulfite. The titanium phosphate modified graphite paste electrode showed a linear response from 2.0 x 10(-3) to 1.0 x 10(-2) mol L-1 with the corresponding equation Y(mu A) = 24.78 + 8.56 x 10(3) [Sulfite], and a correlation coefficient of r = 0.997. The method showed a detection limit of 6.51 x 10(-4) mol L-1 with a relative standard deviation of +/- 5% (n = 3) and amperometric sensitivity of 9.19 x 10(-3) A mol L-1